Work Posture Analysis using the RULA and OWAS Methods in the Cement Packing Section at the Packing Plant Indarung Unit of PT. Semen Padang - Fatimah, Fatimah; Erliana, Cut Ita; Nisa Febriani, Aulia; Chalirafi, Chalirafi (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
PT Semen Padang is a cement manufacturer. According to preliminary observations, the cement packing process, which is done at the Packing Plant Indarung unit, is the last step of the cement production process. Due to the sideways and bowed body positions, cement bagging is performed manually with a less ergonomic working position. This is performed continuously, causing workers complaints of musculoskeletal disorders. The results of distributing the Nordic Body Map questionnaire to employees indicate that many operators experience pain due to their work positions. Based on these findings, the RULA method was used to analyze work posture, yielding a group A posture score of 7, a group B posture score of 4, and a final RULA assessment score of 7. The OWAS method assessment, meanwhile, earned a score code of 2141 and was categorized as a level 3 risk. The results of the risk assessment using the RULA method yield a score of 7, indicating that the operator's work attitude needs to change immediately, whereas the results of the assessment using the OWAS method yield a score of 3, indicating that work posture has a very significant impact on tension and needs to be corrected as soon as possible. On the basis of the results of these assessments, a recommendation was made to design a trolley work facility that can be utilized to reduce the risk of MSDs for cement packaging operators